PROFESSIONAL POLICE OFFICERS BEHAVIOUR IN CRITICAL SITUATIONS - Nedzinskas, Egidijus; Nedzinskienė, Rūta; Šliažienė, Renata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Fast-moving processes in today's society make the importance of prompt, responsible and professional decision-making by police officers. In everyday situations that do not require important and urgent decisions, the police officer can act appropriately and avoid hasty, inadequate decisions. However, the police officer must always be prepared to face an emergency situation, to evaluate it correctly and to use the powers granted to resolve it. The only one wrong decision can have irreversible consequences for the police officer or the public. This paper aims to investigate the behaviour of professional police officers in everyday and critical situations. The research was based on scientific literature analysis and statistical data analysis. One of Lithuanian universities where future police officers are educated has been chosen for the study. A written survey for students – future police officers was performed. The study has shown that police officers, performing their daily duties without the need to take especially important decisions or making critical decisions on which depend the fate of the human, feel the legal liability and social responsibility. In critical situations requiring officers’ self-decision, these decisions are affected by the officers’ sense of responsibility to people, his/her obligation to comply with the law and fear of punishment if the law is violated.